Does HIV-Related Stigma Depress Social Well-Being of Youths Affected by Parental HIV/AIDS? - Zhang, Yafei; Wan, Jiaojiao; Ji, Lili; Liu, Gaigai; Shi, Yixin; Zhao, Junfeng; Li, Xiaoming (Frontiers in Psychiatry, 2022)
Abstract Parental illness or death due to HIV/AIDS has long-term impacts on children’s social well-being, potentially challenging the children’s basic developmental needs and future. Based on the theoretical model of social well-being, the present study tested a moderated mediation model that HIV-related stigma moderated the mediating role of social trust on the relationship between perceived social support (PSS) and social well-being. A sample of 297 youths aged 20-30 years affected by parental HIV/AIDS (57.2% male), including 129 (43.40%) AIDS orphans and 168 vulnerable youths (56.60%) completed questionnaires of perceived social support, social well-being, social trust, and HIV-related stigma. IBM SPSS 25.0 was used to conduct descriptive statistics and multiple regressions. Results showed that the mean score of PSS was 61.34 (SD = 13.99), social well-being was 57.33 (SD = 10.15), social trust was 56.21 (SD = 11.55), perceived stigma was 64.44 (SD = 16.72), and enacted stigma was 21.91 (SD = 9.73) among youths affected by parental HIV/AIDS and the PSS could predict increasing social well-being via increasing social trust. Moreover, the positive influence of PSS on social trust was moderated by the enacted stigma (p = 0.03), in which the positive influence was stronger among youths affected by parental HIV/AIDS who perceived or experienced low enacted stigma than those who perceived or experienced high enacted stigma. The positive impact of social trust on social well-being was moderated by perceived stigma (p = 0.04), in which the positive impact was more significant among youths affected by parental HIV/AIDS who perceived or experienced high perceived stigma than those who perceived or experienced low perceived stigma. These findings explained how and when the PSS affected social well-being and contributed towards an understanding of the experiences and perceptions of HIV-related stigma among youths affected by parental HIV/AIDS. This understanding may inform future research and policies towards improving the social well-being of youths affected by parental HIV/AIDS. The study also highlighted the importance of strengthening interventions on social relations and reducing HIV-related stigma for them.